Interview with Assoc. Prof. Dr. Wan Akil (Deputy Director of Student Affairs) - Maniam, Yuthandy (Universiti Teknologi MARA, Sarawak, 2009)
This article features an interview with Assoc. Prof. Dr. Wan Akil about his new role as Deputy Director of Student Affairs. He shares his initial reaction and explains his main focus-creating a more student-friendly campus. He aims to reduce students' workload from compulsory activities, encourage student-led programs, and improve the use of ICT in administration. He also highlights the importance of building good relationships with students and promoting a positive, harmonious campus environment.